Case Method Model: Strategies for High School Students to Overcome Problems in Learning Poetry - Agustan Agustan (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning poetry serves a variety of purposes, including fostering fluency in spoken language, exposing students to a variety of teaching methods, exposing students to issues of global significance, and fostering an appreciation for different cultures. The purpose of this study is to identify effective strategies for helping high school students learn poetry using a case-method method. The research is a qualitative study. The data analysis procedure used in this study is an objective hermeneutic model which is divided into two analytical procedural models, namely (1) serial analysis and (2) detailed analysis.  The participants were senior high school students from a private Palu high school in the 2022–2023 school year. For this study, thirty youngsters are taking part.  First, students have trouble creating poetry, and second, they have trouble understanding poetry, both of which are significant issues in our research. The study's findings include (1) a case method model that helps students overcome their challenges with poetry writing, and (2) a case method model that helps students overcome their issues with poetry reading. Based on these results, it was determined that using a case method model to address the poetry-learning needs of students in class XI of senior high schools is highly effective in preparing them to produce poetry that adheres to established quality standards. Using proper poetry reading strategies, students are also adept at reading poetry accurately and appropriately.